Co-occurring grazing and climate stressors have different effects on the total seed bank when compared to the persistent seed bank - Espinosa íñiguez, C. (2017)
Questions: (1) Does climate amelioration in semi-arid ecosystems increase seed bank richness and seed density in both total and persistent seed banks? (2) Does herbivory modulate climate effects on soil seed banks? (3) Is this effect mediated by changes in the above-ground vegetation? (4) To what extent do environmental conditions affect similarity between the total and persistent seed banks, and between above-ground (vegetation) vs below-ground (seed bank) community compartments? Location: Ecuadorian Dry Mountain Scrub Ecosystem. Methods: Our study was conducted along a climatic gradient (altitude) under two different management conditions: undisturbed and grazed. The effect of grazing, altitude and their interaction on seed abundance and richness of the total and persistent soil seed banks were evaluated with non-linear mixed models. Results: Altitude, grazing and their interaction exerted a significant effect on richness and abundance of the total seed bank, but not on the persistent seed bank. At highly stressful climate conditions, differences in species richness between the total and persistent seed banks were small or absent, while at milder environmental conditions the total seed bank showed greater seed species richness and abundance than the persistent one. However, under grazing conditions, species richness in both seed banks was rather similar along the climatic gradient. Relationships in terms of species richness between above-ground vs below-ground compartments, shifted from being dominated by the above-ground component at low altitudes (more stress) to being dominated by the seed bank component at higher elevations (milder conditions). In grazed locations, vegetation and seed bank showed similar species richness throughout the altitudinal gradient. Conclusions: This study demonstrates that not only climate acted as a key environmental filter on soil seed bank properties, but also that grazing greatly modulated the primary effect of climate. Nevertheless, the effect of climate and grazing was restricted to the total seed bank (the fertility compartment) and no effect was observed in the persistent seed bank (longevity compartment). In this tropical dry scrub, richness and abundance of seeds increased upwards along the altitudinal gradient, most likely because at higher altitudes environmental conditions improve and become more benign for plant development. We wish to improve our understanding on the effect of plant patch on soil seed bank properties and, more specifically, how these seed reservoirs (seed bank patches) are affected by biotic (i.e. herbivory) and abiotic (i.e. climate) stressors and how they interact with the standing vegetation. Our results showed that although climate is the primary factor determining soil seed bank properties, its effect was profoundly modulated by grazing, as suggested by the existence of an important interaction between both stressors. Not only seed abundance and richness but also the relative dominance of total and persistent seed banks was affected by both environmental stressors. © 2012 International Association for Vegetation Science.